Barriers to E-Commerce Adoption for MSMEs in LAZISMU East Java - Mochamad Mochklas; Dwi Songgo Panggayudi; Anggita Nurhayati (Jurnal Manajemen, 2025)
The growth of e-commerce has become a rapidly growing sector in recent years, but micro, small and medium enterprises (MSMEs) are still lagging in utilising e-commerce. This study aims to analyse the influence of decision-making barriers, technological barriers, organisational barriers, environmental barriers and consumer trust barriers in e-commerce on the business performance of MSMEs fostered by LAZISMU East Java. 226 MSMEs fostered by LAZISMU East Java participated as respondents in this study, and the incoming data was processed using SmartPLS 3.0. The data analysis determined that technological and environmental barriers significantly positively affected the business performance of MSMEs fostered by LAZISMU East Java. Meanwhile, decision-making, organisational, and consumer trust barriers had a positive but insignificant effect on the business performance of MSMEs fostered by LAZISMU East Java.